Design and development of RF power detector for microwave application - Mohamoud Mouse Ali; Siti Zuraidah Ibrahim; Ismahayati Adam; Nurehansafwanah Khalid (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents the design and development of the RF power detector for microwave applications that is operating at 2.4GHz using microstrip. The design of diode detector circuit is simulated using Keysight ADS software tool. The design of the diode detector includes the matching network, Schottky diode and the low pass filter. The paper also presents the fabrication and measurement of the designed circuit.